WhatsApp Use In The Evaluation of Hematuria - ŞENER, TARIK EMRE (ELSEVIER IRELAND LTD, 2018)
Introduction: The advancements in telemedicine provide the possibility to send photos of hematuria cases to professionals for further evaluation. We aimed to evaluate the inter-rater reliability of WhatsApp use in the evaluation of hematuria. Materials and methods: Between December 2014 and April 2016, 212 patients were evaluated prospectively for hematuria by 2 groups of urologists; Group A: in direct contact with patients for evaluation; Group B: blind urologist who had no access to the patients' data but received pictures via WhatsApp. Two photos of voided urine in a sterile container were taken and sent using WhatsApp. The opinions of Group A and B about the grade of hematuria were evaluated. Shapiro-Wilk test and Fleiss' kappa statistics were used for statistical analyses. Results: The median age of patients was 71 (min 22, max 96). The Group A urologists were in accordance in 96.22% of cases. Group B urologists had common opinions in 99.5% (n = 203) and there was almost perfect agreement between 2 groups (lambda = 0.992). The number of common opinions among blind urologists is more than the number of common opinions among the consultants. When further classification is performed as serious and non-serious hematuria, the rate of misdiagnosing serious cases is approximately 6.5-7%. However, using WhatsApp, the urologists can differentiate normal urine and any form of hematuria with 100% accuracy. Conclusion: It is possible to evaluate hematuria remotely and also reduce unnecessary costs of services for hematuria of mild clinical significance by using telemedicine. WhatsApp can provide valuable aid to tertiary hospitals where the urologist is not always present as well as in rural areas.
Keywords: Hematuria; Teleconsulting; Telemedicine; Remote consultation; Decision making; Smartphone; IMPROVING CLINICAL EXAMINATIONS; ORAL MEDICINE CONSULTATION; TELEMEDICINE PLATFORM